From flux to frame : designing infrastructure and shaping urbanization in Belgium. - Van Acker, Maarten (Leuven : University Press, 2014)
Daily traffic jams, discussions whenever a new infrastructure project is launched, the health debate about car emissions The tense relationship between infrastructure and its surroundings becomes clearer to us every day. Infrastructure and urbanism seem to belong to two different worlds. Whilst infrastructure design belongs to the domain of the engineer, urbanism is often part of the overlapping disciplines of architecture, social science, and policy studies.0This book is in the forefront of publications that set out to bridge the gap between those disciplines, and sheds a new light on two centuries of urban planning and transport history. The author investigates the spatial impact of highways, motorways, canals, tramways, and railways on the surrounding landscape by applying a new methodology that combines classical historical literature with innovative mapping techniques. The book features an abundance of previously unpublished historical illustrations of exceptional quality, making this an attractive book for various levels of readership.
boek